ANALYSIS OF THE INFLUENCE OF TRUMP'S IMPORT TARIFFS AND GOLD PRICES ON SHARIA-BASED INVESTMENT DECISIONS - Wahyuni Sirait; Wahyuni; Meliyani; Intan Dinda (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
Islamic financial literacy plays an important role in shaping the financial behavior of the millennial generation, especially in choosing halal financial products. In the midst of the rapid development of the Islamic finance industry, understanding basic concepts such as contracts, usury, and halal-haram limits is essential. This study aims to examine the level of Islamic financial literacy in the millennial generation and its influence on the preference for using halal financial services. Using qualitative methods through literature studies and observations, this study traces the patterns and awareness of millennials in financial decision-making. The results of the study show that a high level of literacy is directly proportional to the use of sharia-compliant products. This indicates that the millennial generation, who have a good understanding, tends to support an ethical and Sharia-based financial system. This study concludes that increasing financial literacy can strengthen the role of millennials in building a sustainable Islamic economic ecosystem in Indonesia.